Suitability of recycled aggregate in fibre reinforced high strength concrete for sustainability - Rao, K. Jagannadha (Journal of Structural Engineering, 2025)
One of the greatest technological challenges of the present day is to utilize the large amount of building and industrial wastes that are generated as a result of infrastructural development. The utilization of these wastes not only save energy and natural resources but also help in controlling environmental pollution. It is well established that aggregate obtained from Construction Demolition Waste (CDW) concrete can be used as coarse aggregate in structural concrete after proper processing. In the present work, an attempt is made to assess the suitability of Recycled Concrete Aggregate (RCA) as an alternative material to natural coarse aggregate for use in high strength structural concrete with and without Alkali Resistant (AR) glass fibres. The feasibility of use of fly ash as partial replacement of cement in RCA concrete to improve properties, to achieve economy and for sustainability is also studied. The grade of concrete adopted in this study was M80. The optimum values of fly ash and RCA contents were arrived at considering the compressive strength of concrete. The various mechanical properties of concrete with optimum RCA and without RCA with varying percentages of glass fibres are compared and optimum fibre content was arrived.